Effect of pirfenidone on mortality: pooled analyses and meta-analyses of clinical trials in idiopathic pulmonary fibrosis. Issue 1 (January 2017) - Nathan, Steven D; Albera, Carlo; Bradford, Williamson Z; Costabel, Ulrich; Glaspole, Ian; Glassberg, Marilyn K; Kardatzke, David R; Daigl, Monica; Kirchgaessler, Klaus-Uwe; Lancaster, Lisa H; Lederer, David J; Pereira, Carlos A; et al.
Summary: Background: In clinical trials of idiopathic pulmonary fibrosis, rates of all-cause mortality are low. Thus prospective mortality trials are logistically very challenging, justifying the use of pooled analyses or meta-analyses. We did pooled analyses and meta-analyses of clinical trials of pirfenidone versus placebo to determine the effect of pirfenidone on mortality outcomes over 120 weeks. Methods: We did a pooled analysis of the combined patient populations of the three global randomised phase 3 trials of pirfenidone versus placebo—Clinical Studies Assessing Pirfenidone in Idiopathic Pulmonary Fibrosis: Research of Efficacy and Safety Outcomes (CAPACITY 004 and 006; trial durations 72–120 weeks) and Assessment of Pirfenidone to Confirm Efficacy and Safety in Idiopathic Pulmonary Fibrosis (ASCEND 016; 52 weeks)—for all-cause mortality, treatment-emergent all-cause mortality, idiopathic-pulmonary-fibrosis-related mortality, and treatment-emergent idiopathic-pulmonary-fibrosis-related mortality at weeks 52, 72, and 120. We also did meta-analyses of these data and data from two Japanese trials of pirfenidone versus placebo—Shionogi Phase 2 (SP2) and Shionogi Phase 3 (SP3; trial durations 36–52 weeks). Findings: At week 52, the relative risk of death for all four mortality outcomes was significantly lower in the pirfenidone group than in the placebo group in the pooled population (all-cause mortality hazard ratio [HR] 0·52 [95% CI 0·31–0·87; p=0·0107]; treatment-emergent all-cause mortality 0·45 [0·24–0·83; 0·0094]; idiopathic-pulmonary-fibrosis-related mortality 0·35 [0·17–0·72; 0·0029]; treatment-emergent idiopathic-pulmonary-fibrosis-related mortality 0·32 [0·14–0·76; 0·0061]). Consistent with the pooled analysis, meta-analyses for all-cause mortality at week 52 also showed a clinically relevant and significant risk reduction in the pirfenidone group compared with the placebo group. Over 120 weeks, we noted significant differences in the pooled analysis favouring pirfenidone therapy compared with placebo for treatment-emergent all-cause mortality (p=0·0420), idiopathic-pulmonary-fibrosis-related mortality (0·0237), and treatment-emergent idiopathic-pulmonary-fibrosis-related (0·0132) mortality; similar results were shown by meta-analyses. Interpretation: Several analytic approaches demonstrated that pirfenidone therapy is associated with a reduction in the relative risk of mortality compared with placebo over 120 weeks. Funding: F Hoffmann-La Roche/Genentech.